Non-canonical Wnt/PCP signalling regulates intestinal stem cell lineage priming towards enteroendocrine and Paneth cell fates - Böttcher, Anika; Büttner, Maren; Tritschler, Sophie; Sterr, Michael; Aliluev, Alexandra; Oppenländer, Lena; Burtscher, Ingo; Sass, Steffen; Irmler, Martin; Beckers, Johannes; Ziegenhain, Christoph; Enard, Wolfgang; et al. (Nature cell biology, 2021)
A detailed understanding of intestinal stem cell (ISC) self-renewal and differentiation is required to treat chronic intestinal diseases. However, the different models of ISC lineage hierarchy 1 – 6 and segregation 7 – 12 are subject to debate. Here, we have discovered non-canonical Wnt/planar cell polarity (PCP)-activated ISCs that are primed towards the enteroendocrine or Paneth cell lineage. Strikingly, integration of time-resolved lineage labelling with single-cell gene expression analysis revealed that both lineages are directly recruited from ISCs via unipotent transition states, challenging the existence of formerly predicted bi- or multipotent secretory progenitors 7 – 12 . Transitory cells that mature into Paneth cells are quiescent and express both stem cell and secretory lineage genes, indicating that these cells are the previously described Lgr5 + label-retaining cells 7 . Finally, Wnt/PCP-activated Lgr5 + ISCs are molecularly indistinguishable from Wnt/β-catenin-activated Lgr5 + ISCs, suggesting that lineage priming and cell-cycle exit is triggered at the post-transcriptional level by polarity cues and a switch from canonical to non-canonical Wnt/PCP signalling. Taken together, we redefine the mechanisms underlying ISC lineage hierarchy and identify the Wnt/PCP pathway as a new niche signal preceding lateral inhibition in ISC lineage priming and segregation. Polarity cues regulate intestinal stem cell fate. Böttcher et al. demonstrate that mouse intestinal stem cells, which express the Wnt/planar cell polarity reporter Flattop, are primed either towards the enteroendocrine or Paneth cell lineage.